(untitled) (Transport systems and technologies, 2018)
Ensuring traffic safety is one of the most important requirements for the operation of railways. Among the accidents and disasters on railway transport, the greatest danger is derailment, as it can lead to grave consequences. The reasons of the derailments of freight flat wagons are connected with malfunctions of rolling stock, deviations from the rules of maintenance of the track, unsatisfactory dynamics of the train as well as the conditions of their operation. According to the results of the tests, it has been established that most of the running dynamic parameters of the platform: the coefficients of vertical and horizontal dynamics, the ratio of the lateral force to the static axle load, the value of vertical and horizontal acceleration, the coefficient of stability from lateral rollover satisfies requirements. The only exception is the index of the coefficient of stability of the wheel from derailment of the flat wagon in idle mode on the straight and curved sections of the railroad in the range of operating speeds, which does not meet the requirements of the normative documentation. To solve the question of determining the safe speed of the flat wagon, dynamic tests have been conducted to determine the coefficient of stability of the wheel from the derailment of the rails in an empty state.